Soft Robotics: Design of Multifunctional Soft Doming Actuator for Soft Machines (Adv. Mater. Technol. 7/2018). Issue 7 (12th July 2018) - Tang, Yichao; Yin, Jie
Abstract : By exploiting the doming deformation in bilayer circular disks, Y. Tang and J. Yin design a soft doming actuator that switches from a flat to dome‐like configuration under pneumatic actuation. In article1800069, they demonstrate how the multifunctional doming actuator can be utilized for underwater swimming, adhesion, and gripping by controlling the doming cavity volume and bending angle at edges.